INFORMATION TECHNOLOGY DEVELOPMENT (WEBSITE) IN SUPPORTING GOVERNMENT COMMUNICATION IN DEPOK CITY, WEST JAVA PROVINCE - Ikhbaluddin, Ikhbaluddin; Kawuryan, Megandaru Widhi (Jurnal Teknologi dan Komunikasi Pemerintahan, 2022)
The focus of this research is the development of information technology in supporting government communication in the city of Depok, West Java Province, more specifically regarding the website of the Government of Depok City, West Java Province. There have been several researches on the websites of regional governments, including; 1. Evaluation of E-Government Implementation on Local Government Websites in Indonesia: Content and Management Perspective by Edwin Arief Sosiawan Fisip UPN Yogyakarta in 2008, 2. Quality Evaluation of Local Government Websites Using the Webqual Method (Case Study in Ogan Ilir District) by Candra Irawan UGM Faculty of Engineering Thesis in 2011, 3. Website Representation of Lampung Provincial Government as a Communication and Public Service Media in the Framework of E-Government By Arlyandi Satya Djauhari Fisip Unila in 2016, and 4. Website usability level on the Banten Province Public Relations Bureau website by M. Ervin Kurniawan Fisip Untirta Banten in 2016, which distinguishes this research when compared to the above research are: 1. This research focuses on the development of information technology in this case the website for public services at the City level, Depok City, 2. This research uses the Alvaro Rocha study (2014) published in the Emerlad Journal which is Scopus indexed, the Rocha (2014) study entitled "Framework for a global quality evaluation of a website". The method in this research is qualitative, in qualitative research with an inductive approach it is easier for researchers to take pictures and describe the facts in the field, then the findings in the field are dissected with various theories that have been prepared. The results of this research are; The Depok City Government has used the website to communicate and provide services to the public, but the website needs some improvements, among others; 1. The renewal of information on the website needs to be improved, 2. Community complaints need to be answered immediately, 3. Depok City Communication and Information Agency needs to be given more authority to gather information spread across several agency 4. Website maintenance needs to be considered because there are several pages that cannot be opened. Keywords: Public Service, Communication, Website, Information Technology.